2022
DOI: 10.3889/oamjms.2022.7645
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ View towards the Use of Robotic during Pandemic COVID-19 in Indonesia: A Qualitative Study

Abstract: Background: Rapid advances in artificial intelligence and robotics have alleviated difficulties for patients, hospitals, and the industry as a whole. However, the health care system is identically human-centered at its core, and many healthcare professions may not be ready to work with robots. Understanding nurses' views toward robotics can help integrate robotic technologies into future patient care. Objectives: This study aimed to explore how nurses view using robotics during the COVID-19 pandemic.�… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…The results showed that the nurses's attitude toward meeting the self-care roles, counseling, protecting the individual, respecting the individual's rights, and their role in the treatment process was positive. In contrast, the study conducted by Taryudi et al investigated the nurses' attitudes toward the utility of robots and found a negative outlook on their role in managing the COVID-19 outbreak (Taryudi et al, 2022). We also found that the attitude of the nurses toward their caregiving roles (nurse safety, self-care, and treatment) was positive despite fear of transmitting the COVID-19 infection, contracting the infection, and death.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The results showed that the nurses's attitude toward meeting the self-care roles, counseling, protecting the individual, respecting the individual's rights, and their role in the treatment process was positive. In contrast, the study conducted by Taryudi et al investigated the nurses' attitudes toward the utility of robots and found a negative outlook on their role in managing the COVID-19 outbreak (Taryudi et al, 2022). We also found that the attitude of the nurses toward their caregiving roles (nurse safety, self-care, and treatment) was positive despite fear of transmitting the COVID-19 infection, contracting the infection, and death.…”
Section: Discussioncontrasting
confidence: 60%
“…Several collaborative robots developed and used during COVID-19 were able to perform certain routine duties of a nurse, such as recording vital signs from the bedside monitor and transferring data collected from patients to the healthcare team (Dickens & Cook, 2006;Lin, Abney, & Bekey, 2011;Sharkey & Sharkey, 2012). A study examined the attitude of nurses toward the utility of robots as negative in managing the COVID-19 outbreak (Taryudi et al, 2022). The other study reported that nurses had a negative attitude toward the use of robots for nursing care activities, but a generally positive attitude toward their use for service, monitoring, and communication tasks (Sharts-Hopko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the results of the present study, in their study conducted to investigate healthcare professionals' perceptions of and attitudes towards the application of AI technologies in healthcare institutions in Saudi Arabia, Abdullah and Fakieh (2020) reported that most of the participants were worried that AI would take over their jobs (Abdullah & Fakieh, 2020). In their study, which was aimed at investigating how nurses in Indonesia viewed the use of robotics during the COVID‐19 pandemic (2022), Taryudi et al (2022) reported that in the future, robots would take over nurses' jobs and that using robots would reduce nurse skills.…”
Section: Discussionmentioning
confidence: 99%
“…72% considered themselves well-oriented, 70% heard about AI applications, and 24% reported well knowledge about AI. Our study’s knowledge is less than Swan’s results as 40% agreed they have AI knowledge while almost similar in the basic understanding (Table 1 ) [ 5 , 13 ]. Interim of attitude, perceptions and implications both studies showed the excitement of the nurses towards integrating AI application in daily work practice.…”
Section: Discussionmentioning
confidence: 53%
“…The nursing profession is critical in healthcare delivery as it works directly with the patients and ensures the diagnostic and treatment plans work efficiently. The daily nursing tasks are wide and varied and include maintaining the patient charting, recording, taking vital signs, assisting in physical exams, and communication between patients, physicians, other healthcare professionals, and administrator’s sectors [ 13 ]. Therefore, there is no question that the impact of AI in nursing practice will be transformational.…”
Section: Discussionmentioning
confidence: 99%